Comprehensive Laboratory Benchmark of K-shell Dielectronic Satellites of Fe xxv–xxi Ions - Chintan Shah; Pedro Amaro; Filipe Grilo; Ming Feng Gu; Liyi Gu; José Paulo Santos; F. Scott Porter; Thomas Pfeifer; Maurice A. Leutenegger; José R. Crespo López-Urrutia (The Astrophysical Journal, 2025)
We report on comprehensive laboratory studies of the K-shell dielectronic recombination resonances of Fe xxv – xxi ions that prominently contribute to the hard X-ray spectrum of hot astrophysical plasmas. By scanning a monoenergetic electron beam to resonantly excite trapped Fe ions in an electron beam ion trap and achieving a high electron–ion collision energy resolution of ∼7 eV, we resolve their respective KL n satellites up to ${n}^{{′} }=11$ . By normalization to known radiative recombination cross sections, we also determine their excitation cross sections and that of the continuum with uncertainties below 15% and verify our results with an independent normalization based on previous measurements. Our experimental data excellently confirm the accuracy and suitability of distorted-wave calculations obtained with the Flexible Atomic Code for modeling astrophysical and fusion plasmas.